Comparative pharmacokinetics of ceftriaxone and tazobactam (8:1) between healthy and Escherichia coli induced diarrhoeic birds - Mithin U.C; Rinku Buragohain; Pradip Das; Tapan Mandal; Rabindra Hansda; Siddhartha Joardar; Indranil Samanta; Tapas Sar (International Association of Physical Chemists (IAPC), 2022)
Antibiotic-resistant Escherichia coli infection of poultry causes significant economic losses. Extended spectrum β lactamases (ESBL) producing E. coli was inoculated in a broiler, Rhode Island Red and Haringhata Black birds orally at 56×108 c.f.u. mL-1 for induction of diarrhoea. Pharmacokinetics of ceftriaxone-tazobactam combination (8:1) was studied following a single intramuscular injection at 28.125 mg kg-1 and the combination was administered twice daily to treat such infection. Plasma concentration of both ceftriaxone persisted up to 8 h in experimental birds and maintained an approximate ratio of 8:1 with tazobactam for a period of 2 h, 0.25 h and 0.75 h, respectively in a broiler, Rhode Island Red and Haringhata Black birds. The Kel was significantly lower in all experimental birds compared to healthy birds. Efficacy study was conducted in diarrhoeic birds by administration of ceftriaxone-tazobactam combination at 28.125 mg kg-1 body weight twice daily intramuscularly for three days which caused an increase in specific antibody titre in the broiler on 5th day and in Rhode Island Red birds 10th day. However, Haringhata black birds were inherently showed more resistance towards the infection. The combination of ceftriaxone and tazobactam in the ratio of 8:1 can be an effective treatment to combat ESBL producing E. coli infections.